The Application of 3S Technology to the Tsukuba Bailin Landscape Project - Xu, Hao (International Journal of Online and Biomedical Engineering (iJOE), 2013)
The purpose of this paper is to investigate the method and process of using 3S technology on a landscape engineering project. Through a case study on the Bailin landscape construction project in Tsukuba, Japan, this paper argues that strengthening the drafting capabilities of 3S technology (e.g., comprehensive database management, mapping, landscape simulation, and data updating) will create the type of integrated platform for engineering design and management needed to increase the efficiency of landscape engineering projects.